Older People in Sweden Without Means: On the Importance of Age at Immigration for Being 'Twice Poor' - Björn Anders Gustafsson; Hanna Mac Innes; Torun Österberg (Institute of Labor Economics (IZA), 2017)
This paper examines immigrant poverty at an older age in Sweden with an emphasis on late-in-life immigrants. We analyse tax data for the entire Swedish-born and non-Swedish-born population. The poverty status of a household is assessed using two criteria. First, the disposable income of the household in which the person lived in 2007 must be below 60 per cent of the median equivalent in-come in Sweden as a whole. Second, to be classified as 'twice poor' a household net assets must be below SEK 10,000. The results indicate that three out of four Swedish-born older persons were not classified as poor by either of the criteria, and only one per cent by both criteria. In contrast, among older persons born in low-income countries almost three out of four were classified as poor according to one of the criteria and not fewer than one in three according to both. Results of estimating logistic models indicate that the risk of being considered poor according to both criteria is strongly positively related to one's age at immigration. Our results indicate that it is crucial that migrants, particularly those who arrive after age 40, be better integrated into the Swedish labour market. To alleviate pov-erty among those migrants who are already of older age, increased transfers are probably the only possible alternative.
Keywords: I32; J14; J15; 330; older people; poverty; immigrants; Sweden